Applying the Lesson Study Model in Developing Teaching Capability for Young Teachers in Vietnam - Le Thi Thu Huong (RU Publications, 2021)
The initial period of young teachers' careers is always significant in developing their professional capability. This is when teachers start coming into contact with practical teaching, which is more diversified than the theoretical training at the University. In this research, the authors propose a process of combining the Lesson Study model with the micro-lesson teaching method. This process helps young teachers, especially those working in the Northern of Vietnam, improve their planning and implementation of a lesson plan following the Lesson Study model. It has four steps: (1). Plan a Lesson Study; (2). Organize demo teaching and attend lessons; (3): Self-evaluate and discuss lessons; (4): Apply for practical teaching. The methodology research is carried out on 62 young teachers in Vietnam to measure the pre-impact and post-impact results. The results reveal that the researched group has made significant progress on their teaching performances (the average points for their capability of planning lessons have increased from 2.54 to 3.28 and the average points for their capability of implementing lesson plans have increased from 2.48 to 3.18). This development can be considered as an excellent experience to bring the Lesson Study model into Vietnamese schools to improve teaching sustainably.